N-TERMINAL PRO-B-TYPE NATRIURETIC PEPTIDES IN INFANTS AND CHILDREN WITH NON-CARDIAC DISEASES - Ali, Humaira; Alam, Junaid M; Naureen, Shazia (Pakistan Armed Forces Medical Journal, 2021)
Objective: To evaluate the levels of N-terminal pro-B-type Natriuretic Peptide in infants and children with non-cardiac diseases especially respiratory diseases. Study Design: Cross-sectional study. Place and Duration of Study: Department of Chemical Pathology/Biochemistry Laboratory Services of Liaquat National Hospital Karachi Pakistan, from Dec 2018 to Nov 2019. Methodology: Infants and children admitted to the Pediatric department with non-cardiac diseases were included in the study. Non-probability consecutive sampling was done. Blood was taken and analyzed for N- terminal pro-B-type Natriuretic Peptide, Troponin I, urea, creatinine, Lactate dehydrogenase, Creatinine Kinase, lactate and sodium analysis. Results: Out of the 93 patients, 74 (80%) were diagnosed with respiratory disorders, with bronchopneumonia making up 54 (59%) Bronchiolitis 15 (17%) and 4% had miscellaneous respiratory diseases. Out of the remaining 20%, 8 (9%) patients were diagnosed with sepsis, and the remaining 11% were diagnosed with miscellaneous diseases. There was a positive correlation of N- terminal pro-B-type Natriuretic Peptide with Troponin I, urea, creatinine, Creatinine Kinase and Lactate dehydrogenase levels (p<0.05). Conclusion: N- terminal pro-B-type Natriuretic Peptide levels were found to be raised in pediatric patients with non-cardiac diseases especially broncho-pneumonia and in future it may be used as a marker of bronchopneumonia in children.